Do Conditional Cash Transfers Empower Women? Insights from Brazil's Bolsa Família. (May 2020) - Sugiyama, Natasha Borges; Hunter, Wendy
ABSTRACT: Conditional cash transfer programs (CCTs) have emerged as an important social welfare innovation across the Global South in the last two decades. That poor mothers are typically the primary recipients of the grants renders easy, but not necessarily correct, the notion that CCTs empower women. This article assesses the relationship between the world's largest CCT, Brazil's Bolsa Família, and women's empowerment. To systematize and interpret existing research, including our own, it puts forth a three-part framework that examines the program's effects on economic independence, physical health, and psychosocial well-being. Findings suggest that women experience some improved status along all three dimensions, but that improvements are far from universal. A core conclusion is that the broader institutional context in which the Bolsa Família is embedded—that is, ancillary services in health and social assistance—is crucial for conditioning the degree of empowerment obtained.